Integrating Nutritional Medicine into Medical Studies - A Model Curriculum: Model Curriculum of the German Society for Clinical Nutrition and Metabolism (DGEM a/Young DGEM a), the Association of German Nutritionists (BDEM b) and the German Academy of Nutritional Medicine (DAEMc) Ernährungsmedizin im Studium der Humanmedizin -Mustercurriculum: Mustercurriculum der Deutschen Gesellschaft für Ernährungsmedizin (DGEM a/Junge DGEM a), des Berufsverbandes Deutscher Ernährungsmedizinerinnen und Ernährungsmediziner e. V. (BDEM b) und der Deutschen Akademie für Ernährungsmedizin e. V. (DAEMc) - Hill, Aileen; Leineweber, Can Gero; Wechsler, Johannes; Stehle, Peter; Von Ellerts, Antonia; Sester, Lilli; Dresen, Ellen; Cittadino, Jonas; Adam, Olaf; Kauth, Thomas; Herbers, Jürgen; Bischoff, Stephan C.; et al. (Aktuelle Ernährungsmedizin, 2025)
This model curriculum for nutritional medicine in the human medicine program was developed through an interprofessional and multidisciplinary approach, involving authors from various educational backgrounds and professional societies. Nevertheless, the presented outcome should be viewed as a suggestion and as ongoing. The group of authors invites interested readers to participate in this process.
CRIS-Team Scopus Importer:2025-12-05
Keywords: Curriculum; medical education; nutritional medicine; physicians; students